The Art of Storytelling in Science: A Personal Journey - Bruno Bezerril Andrade (Journal of Medical Education and Curricular Development)
Storytelling is a crucial yet often overlooked skill for scientists, essential in seminars, manuscripts, grant applications, and professional interactions. Drawing from my experiences across Brazil, the United States of America, India, and South Africa, I explore how crafting compelling narratives enhances scientific communication, increasing the likelihood of publishing, securing funding, and building collaborations. Reflecting on formative “hot seat” sessions at the National Institutes of Health, in the United States, I emphasize the importance of structuring ideas clearly, regardless of language fluency. Storytelling brings clarity, engagement, and logic to science, making research more relatable and impactful. Mastering this skill is essential for advancing scientific careers and effectively conveying complex ideas.